On distributed codes with noisy relays - Thobaben, R. (2008 42nd Asilomar Conference on Signals, Systems and Computers, 2008)
In this paper, we address the design of distributed coding schemes for the 3-node relay channel with half-duplex constraint. We first discuss the general problem of optimally re-encoding noisy data at the relay and summarize recently proposed approximations. Based on an analysis of the extrinsic information transfer characteristics of the component codes we investigate the potential of ldquoweakrdquo turbo or LDPC codes which are employed by the source node in order to increase the reliability of the relay when decoding is not possible. The results show that we can indeed gain from the proposed code design.